2022
DOI: 10.1002/pcn5.45
|View full text |Cite
|
Sign up to set email alerts
|

White matter alterations in the dorsal attention network contribute to a high risk of unsafe driving in healthy older people

Abstract: Aim: Healthy older drivers may be at high risk of fatal traffic accidents. Our recent study showed that volumetric alterations in gray matter in the brain regions within the dorsal attention network (DAN) were strongly related to the risk of unsafe driving in healthy older people. However, the relationship between white matter (WM) structural connectivity and driving ability in healthy older people is still unclear. Methods:We used diffusion tensor imaging to examine the association between microstructural alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…In particular, I found that rsFC and risk-rating tbFC significantly predicted driving violations, and the dorsal attention, frontal-parietal, and subcortical networks were revealed as the most common contributing networks. This was consistent with previous studies where gray and white matter in the dorsal attention network were shown to be associated with a high risk of unsafe driving [ 42 , 43 ]. Furthermore, the dorsal attention network has been shown to play a role in the control of stimulus-driven, goal-directed [ 44 ], and top-down control of attention [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…In particular, I found that rsFC and risk-rating tbFC significantly predicted driving violations, and the dorsal attention, frontal-parietal, and subcortical networks were revealed as the most common contributing networks. This was consistent with previous studies where gray and white matter in the dorsal attention network were shown to be associated with a high risk of unsafe driving [ 42 , 43 ]. Furthermore, the dorsal attention network has been shown to play a role in the control of stimulus-driven, goal-directed [ 44 ], and top-down control of attention [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 93%